Well measurement data 2001-2015 - Hobbs, Tom; Kotter, Dan (Colorado State University. Libraries, 2016)
Water tables measurements collected at wells at willow sites in Yellowstone's Northern Range. Data file contains manual well measurements during spring, summer, and fall.
Zip file includes: data and metadata file.
Natural Resource Ecology Laboratory (NREL)
Keywords: groundwater